Home and Homeland : the Dialogics of Tribal and National Identities in Jordan. - Layne, Linda L. (Princeton University Press, 2001)
In this provocative examination of collective identity in Jordan, Linda Layne challenges long-held Western assumptions that Arabs belong to easily recognizable corporate social groups. Who is a "true" Jordanian? Who is a "true" Bedouin? These questions, according to Layne, are examples of a kind of pigeonholing that has distorted the reality of Jordanian national politics. In developing an alternate approach, she shows that the fluid social identities of Jordan emerge from an ongoing dialogue among tribespeople, members of the intelligentsia, Hashemite rulers, and Western social scientists. Man.